Development of validated stability-indicating HPTLC method for the estimation of ulipristal acetate in bulk and dosage form - Shruti Srivastava, Suneela Dhaneshwar, Neha Kawathekar (Journal of Applied Pharmaceutical Science, 2021)
The stability-indicating method is a validated analytical method which accurately and precisely measures the active ingredients from degradation products, excipients, and process impurities. The present study establishes the development of validated stability-indicating high performance thin layer chromatography method for the analysis of ulipristal acetate (UPA) in bulk and in dosage form with the help of the International Conference on Harmonization guidelines. Separation on pre-coated silica gel 60F254 plates was achieved using mobile phase of dichloromethane: methanol (9.5:0.5; v/v). The densitometric scanning was carried out at the absorbance mode of 312 nm. The aimed method was found linear with a correlation coefficient of 0.998 in the concentration of 30–150 ng/spot. The estimated values of limit of detection and limit of quantification were found to be 9.57 ng/spot and 29.022 ng/spot, respectively. Forced degradation studies of UPA indicated its degradation under acidic, alkaline, oxidative, thermal, and photolytic stress conditions. The degradants were resolved from the pure drug significantly at different Rf values. The developed method can be used for identification, quantitative determination, and for monitoring the stability of UPA in the presence of its degradants in bulk and formulation.
Keywords: Degradation study, dichloromethane, ICH guideline, methanol, ulipristal acetate.